The Architecture of Working Memory: Features from Multiple Remembered Objects Produce Parallel, Coactive Guidance of Attention in Visual Search - Bahle, Brett (J Exp Psychol Gen, 2019)
Theories of working memory (WM) differ in their claims about the number of items that can be maintained in a state that directly interacts with other, ongoing cognitive operations (termed the focus of attention). A similar debate has arisen in the literature on visual working memory (VWM), focused on the number of items that can simultaneously interact with attentional priority. In three experiments, we used a redundancy-gain paradigm to provide a comprehensive test of the latter question. Participants searched for two cued features (e.g., a color and a shape) within a search array. The cued feature values changed on a trial-by-trial basis, requiring VWM. The target (when present) could match one of the cued features (single-target trials) or both cued features (redundant-target trials). We tested whether response time distributions contained a substantial proportion of trials with redundant-target responses that were faster than predicted by two independent guidance processes operating in parallel (i.e., violations of the race-model inequality). Violations are consistent with a coactive architecture in which both cued values guide attention in parallel and sum on the priority map. Robust violations were observed in all cases predicted by the hypothesis that multiple items in VWM can guide attention simultaneously, and these results were inconsistent with the hypothesis that guidance is limited to a single item simultaneously. When considered in the larger context of the literature on VWM and attention, the present results are consistent with a model of WM architecture in which the focus of attention can maintain multiple, independent representations.